STUDI KERUSAKAN LINGKUNGAN AKIBAT PENAMBANGAN BGGC WILAYAH SUNGAI DI KABUPATEN PEKALONGAN - Najib Najib (TEKNIK, 2011)
Pekalongan Residence has a relatively many sand and gravel deposits particularly in river area. Nowadays,many locations have been exploited by local residences or investors from other regions. Sand and gravel miningis being done since 1980s, that’s why it can created devastated land in that surrounding area of mining. As theresult of that condition, it is called for the research to determine how devastated land condition during or aftermining. Factors used in this research to determine devastating land are mining technique, rate of mining, depthof slope mining, width of mining hole, relief of digging base, characteristics of material slope, tilt of diggingslope, reserving of top soil and overburden, erosion stage, vegetation cover, reclamation. Devastated landbased on mining has vary in low and high scale. In the gullies river,most of them in low devastated landcondition. Meanwhile, devastated land in border of river vary in low up to high. Several places which are havehigh devastated land are Sastrodirjan (Wonopringgo District), Dororejo(Doro District) and Krompeng (TalunDistrict). In deposit bar, has low up to high devastated land. High devastated land are Pododadi (Karanganyardistrict), Sastrodirjan (Wonopringgo district) and Kaligawe (Karangdadap district).